Теория и практика разработки тестовых материалов: учебное пособие - Михайлова Н. С. Наталья Степановна; Минин М. Г. Михаил Григорьевич; Муратова Е. А. Елена Анатольевна; Илюхин Б. В. Борис Валентинович (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана